2000
DOI: 10.1111/j.1525-1373.2000.22334.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Toxic Heavy Metals Across Cell Membranes

Abstract: Abstract. Membrane transport of nonessential toxic heavy metals (type D heavy metals) not only controls their access to intracellular target sites but also helps determine their uptake, distribution, and excretion from the body. The critical role of membranes in the toxicology of class D metals has attracted the attention of many investigators, and extensive information has been collected on the mechanism(s) of metal transfer across membranes. Characteristics of metal transport in different cells, or even on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
(53 reference statements)
0
15
0
2
Order By: Relevance
“…On a cellular level, the interaction of heavy metals with cell membrane transport mechanisms is the basis for their effect on biological systems. Examples of this interaction are given by Foulkes [50], describing the internalization of metals inside the cell, and Yu et al [51], describing an alteration of the activity of epithelial sodium channels (ENaC) following divalent heavy metals exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a cellular level, the interaction of heavy metals with cell membrane transport mechanisms is the basis for their effect on biological systems. Examples of this interaction are given by Foulkes [50], describing the internalization of metals inside the cell, and Yu et al [51], describing an alteration of the activity of epithelial sodium channels (ENaC) following divalent heavy metals exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the latter authors reported that the mechanism of toxin action mainly depends on pore-forming into the membrane of cell target rather than oxidative damage, since GSH, cysteine and ascorbic acid did not impair the hemolytic power. Based on these observations, an intriguing hypothesis is that the interaction of metals with cell membrane [50] or crude venom components may reduce the hemolytic activity of venom by impairing the binding and insertion of pore-forming toxins in the membrane of target cells. Accordingly, Miyake et al [62] explained the inhibitory effect of divalent cations upon Vibrio metschnikovii cytolysin by changes in the erythrocytes membrane fluidity, so that pore formation due to the toxin was impaired, while, on the other hand, Iwase et al [63] suggested that extracellular Ca 2+ may accelerate the rate of removal of the toxin by endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Для нормальной жизнедеятельности рас-тениям необходимы: медь, никель, цинк, железо, марганец, кобальт [9]. Медь входит в состав фер-ментов, осуществляющих окислительно-восстано-вительные реакции ( аскорбатоксидазы, суперок-сиддисмутазы, цитохромоксидазыc и др.).…”
unclassified
“…Как правило, тя-желые металлы не находятся в цитоплазме клеток в свободном состоянии, а лишь в форме хелатов [9,11]. У растений хелатирующими агентами для тяжелых металлов являются: фитохелатины, ме-таллотионеины, карбоновые и аминокислоты.…”
unclassified
“…The cutaneous manifestations of arsenical toxicity are hypopigmentation, hyperpigmentation and keratosis, mainly on the palms and soles. [3][4][5][6][7][8] All these conditions have been described in endemic chronic hydroarsenicosis. Also, arsenic has been recognized as a cutaneous carcinogenic agent [9][10][11][12][13][14] in basal cell carcinoma, epidermoid carcinoma and Bowen's disease.…”
mentioning
confidence: 99%